2020
DOI: 10.1152/japplphysiol.00828.2019
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglossal nerve stimulation in a rabbit model of obstructive sleep apnea reduces apneas and improves oxygenation

Abstract: Based on a prior anesthetized model, we developed an unanesthetized model to evaluate the effects of hypoglossal nerve stimulation (HNS) during sleep. We prepared three rabbits with injections of Hyaluronic Acid in the base of tongue to produce upper airway obstruction followed by HNS implant. Two rabbits were saline controls, and one, a passive control. Measures were sleep, airflow, effort, oxygen saturation and heart rate. HNS with electrodes around the right hypoglossal nerve were adjusted to a level withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The disturbed activity of the hypoglossal motoneurons contributes to the development of obstructive sleep apnea syndrome (OSA) [ 21 , 37 ]. In support of this, numerous scientific reports showed that stimulation of the HG nerve in humans and animals has the benefit of a reduced number of pauses in breathing during sleep [ 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 97%
“…The disturbed activity of the hypoglossal motoneurons contributes to the development of obstructive sleep apnea syndrome (OSA) [ 21 , 37 ]. In support of this, numerous scientific reports showed that stimulation of the HG nerve in humans and animals has the benefit of a reduced number of pauses in breathing during sleep [ 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 97%
“…Most importantly, unlike other animals and like the human, the hyoid bone of the rabbit is mobile with no fixed bony attachments ( Amatoury et al, 2014 ; Amatoury et al, 2015 ). The rabbit model has also been repeatedly used in the fields of respiratory and upper airway physiology with demonstrated applicability of outcomes to humans ( Brouillette and Thach, 1980 ; Olson et al, 1989 ; Isono et al, 1997 ; Kirkness et al, 2003a ; Kirkness et al, 2003b ; Fogel et al, 2005 ; Kairaitis et al, 2006 ; Squier et al, 2010 ; Kairaitis et al, 2012 ; Amatoury et al, 2014 ; Amatoury et al, 2015 ; Amatoury et al, 2016 ; Schiefer et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is a feasible idea to establish an OSA animal model by injecting dilatants (such as polytetrafluoroethylene and hydrophilic polyacrylamide gel) into soft tissues of the upper airway, such as the tongue or the soft palate, which can cause persistent swelling and narrowing of the upper airway soft tissues (32)(33)(34)(35)(36)(37). Polytetrafluoroethylene (PTFE) is an inert swelling agent used in the treatment of vesicoureteral reflux.…”
Section: Spontaneous Upper Airway Narrowing Modelmentioning
confidence: 99%